Valuation in the dark: constructing perceptions of normality in failing markets. Issue 4 (June 2019) - Adams, David; Tolson, Steven
Abstract : This paper explores the challenging task of assigning value to land in 'thin' or 'fragile' property markets characterised by economic restructuring and capital flight. Such markets are frequently epitomised by low demand and substantial uncertainty. The paper draws on detailed interview evidence with professional valuers to reveal the difficulties they experience in seeking to apply traditional valuation methods in one such failing market. Reliance on their own experience and professional judgement reinforces the role of valuers as market makers with the desire to uphold perceptions of normality by placing a value on land that theoretically might appear to have none.